(untitled) (Journal of the College of Basic Education, 2024)
This research presents the phenomenon of referral in cognitive linguistics. especially in the mental space theory , that referral relied on mechanisms of procedural function grammar. I thought it would be in a novel with a nature approaching the curriculum vitae to be grounded for application, the first is due to the fact that cognitive linguistics pay more attention to the mental references, social, psychological, and cultural contexts of the sender and how to deal with all forms of referrals. Second is that the novel contains many self-references that can be used as in the study was based on what functional grammar produced and benefited from cognitive grammar